The east-to-west decay of math and reading scores in the United States: A prediction from UVB radiation theory - León Eyzaguirre, Federico R. (2015)
According to a novel theory, latitude influences complex cognitive ability through hormonal and dopaminergic effects of UVB radiation on family size and study habits. Since human exposure to UVB radiation increases from East to West in the United States, longitude can be expected to influence White children's math and, especially, reading scores. Analyses of National Assessment of Educational Progress (NAEP) State data showed greater effects of longitude on Reading than Math and a decay of influence from 4th to 8th grades; latitude's influence was analogous on Math and Reading and increased across grades. The findings are consistent with the theory that, in the United States, longitude influences cognitive abilities through parents' sexual hormones, family size and early in life; they also suggest that latitude exerts influence mainly through dopamine deficiency and study habits and cumulatively.